African fossiliferous amber: a review - (:unkn) unknown (My University, 2016)
Amber has only rarely been found in Africa and the few known occurrences aremostly devoid of organic inclusions. The first fossiliferous African amber wasreported a few years ago from Ethiopia, and was considered to be early LateCretaceous in age (Cenomanian, ~93-95 Ma). However, recent investigation ofadditional amber material and associated sediment questions the previously assumedage and provides compelling evidence that Ethiopian amber is Cenozoic, likelyMiocene. Support for this dating is based on both new and revised palynologicaland palaeoentomological data. Insect fossils mostly belong to extant families andgenera. A particular reference to ants (Hymenoptera: Formicidae) is made here, withthe report of 51 individuals assignable to new extinct species of Dolichoderinae(e.g. Technomyrmex), Formicinae, Myrmicinae (e.g. Melissotarsus, Carebara),Ponerinae and Pseudomyrmecinae (e.g. Tetraponera). Chemical analysis indicatesthat Ethiopian amber belongs to the Class le ambers typical of Fabaceae (althoughthe earliest record of a Class le amber dates back to the Carboniferous) and waspresumably produced by the genus Hymenaea, similar to East African Pleistocenecopals and Neotropical Miocene' ambers. Although much younger than previouslysuggested, fossils in Ethiopian amber remain highly relevant as Miocene insects areexceedingly rare in Africa.The recent discovery of a new deposit offossiliferous amber is also reportedhere, from the Early Cretaceous (Aptian, 113-117 Ma) of Congo-Brazzaville.Chemically, Congolese amber belongs to the Class Ib typical of conifers, and thefamily Cheirolepidiaceae is assumed to be the plant source. Amber nodules are darkred in colour, with large pieces reaching up to 12 cm. The search for organismicinclusions using conventional optical techniques is limited by the opacity of theamber, but diverse arthropods and plant remains have already been found in fewmore translucent pieces. A large survey using synchrotron imaging will
Keywords: African Research